Flow Planning Sistem Trayek dan Manajemen Pengangkutan Sampah di Kelurahan Gurabati - Altarans, Indra; Faruk, Fitriyanti; Yahya , M Taurid (Penerbit Goodwood, 2024)
Purpose: The aim of empowerment is to plan Flow Planning for the route system and waste transportation management in Gurabati Subdistrict, so that the transportation system is designed with a clear transportation route planning flow so as to minimize residents throwing garbage in the sea and rivers. Methodology: The method of empowerment is to schedule waste transportation times and waste transportation service routes and enforce regulations issued by the Gurabati District government against people who throw garbage carelessly. Results: The result of this service is a fixed transportation schedule, namely three times a week with scheduled transportation times in the afternoon, namely 04.00 in the afternoon to 06.00 in the afternoon. Apart from that, rescheduling the waste transportation system in each RW. Scheduling of waste transportation to be transported by officers, in the morning and afternoon. And the need for strong regulations from the Gurabati sub-district government. Training is also supported to improve capabilities. Conclusions: The community service team implemented a route system approach for waste collection, ensuring that waste is transported properly. However, waste collection officers must strictly follow the planned route system to ensure that waste from each RW is fully collected. Even though a well-planned waste transportation system is in place, the accumulation of waste in Gurabati Village is still likely to occur due to the need for more temporary storage capacity. Limitations: The limitations experienced in carrying out services are the very limited number of transport fleets and officers. If you look at its size, Gurabati Village itself consists of four RWs. Judging from the transportation system analysis, two RWs are needed consisting of one fleet and two waste transport workers. Contribution: Community service activities in Burai show that the contribution of this service is increasing Sogrohogam Partners' knowledge regarding appropriate waste transportation service flows, so that the waste service flow can run well and everything in the Globalti sub-district can be transported as a whole.